Association of partner, parental, and employment statuses with self-rated health among German women and men - Elena von der Lippe; Petra Rattay (Elsevier, 2016)
The association of partner, parental, and employment statuses with health is usually discussed in terms of either the multiple role burden hypothesis or the multiple role attachment hypothesis. The first hypothesis states that combining work and family roles increases the burden of responsibility, which in turn increases the pressure and stress associated with competing roles, leading to poorer health. The multiple role attachment hypothesis argues that multiple responsibilities provide attachment to broader networks, which then provide social support and resources that enhance health.We analyzed pooled data from the German Health Update carried out by the Robert Koch Institute in 2009, 2010, and 2012. The data were collected by computer-assisted telephone interviews. The sample comprised 28,086 people aged 30-54 years. The data were assessed with logistic regression analysis and interaction models. The gender-differentiated analysis of partnership, parenthood, and employment, after adjusting for social and demographic characteristics, revealed small interaction effects among all three social roles with self-rated health in women and men.Non-employment showed the strongest relationship with poor self-rated health. It was significantly associated with lower self-rated health in both men and women in most of the family arrangements. These associations were higher in men than in women. Furthermore, in all family arrangements, female part-time employees were as healthy as female fulltime employees. A more subtle association was found in men: the odds of reporting poorer self-rated health were greater among non-parents employed part time than among those employed full time, but lower than among those who were non-employed. Among fathers, part-time employees did not have statistically better health than full-time employees.The findings support somewhat the multiple role attachment hypothesis, rather than the multiple role burden hypothesis. Because employment has great importance for both women's and men's health, the compatibility of work and family roles should be improved.